2009
DOI: 10.1523/jneurosci.3811-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Exerts Contrasting Effects on Peripheral Myelination of NGF-Dependent and BDNF-Dependent DRG Neurons

Abstract: Although brain-derived neurotrophic factor (BDNF) has been shown to promote peripheral myelination during development and remyelination after injury, the precise mechanisms mediating this effect remain unknown. Here, we determine that BDNF promotes myelination of nerve growth factor-dependent neurons, an effect dependent on neuronal expression of the p75 neurotrophin receptor, whereas BDNF inhibits myelination of BDNF-dependent neurons via the full-length TrkB receptor. Thus, BDNF exerts contrasting effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 26 publications
3
75
0
Order By: Relevance
“…A recent study by Xiao et al (27) demonstrated that BDNF promoted myelination through p75 from the neuron side and MO1 reduces Pard3 protein levels and inhibits RacGTP levels in zebrafish larvae. Embryos at 4 dpf were deyolked, and proteins were extracted for RacGTP assays and control Western blot analyses.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Xiao et al (27) demonstrated that BDNF promoted myelination through p75 from the neuron side and MO1 reduces Pard3 protein levels and inhibits RacGTP levels in zebrafish larvae. Embryos at 4 dpf were deyolked, and proteins were extracted for RacGTP assays and control Western blot analyses.…”
Section: Discussionmentioning
confidence: 99%
“…DRG neuron populations are heterogeneous with regard to the quality of sensory transmission, and different growth factors act selectively on different subpopulations of DRG neurons. [26][27][28][29] Therefore, an emerging concept in the field of artificial nerve graft development is to use a combination of NTFs with the aim to obtain a widespread effect on all sensory, motor, and sympathetic neuronal subpopulations. [30][31][32] It is, however, still under debate which NTF combination will result in the most successful support of PNR while simultaneously avoiding negative influences in the process.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the OPC seeding, completely aspirate media from the DRG culture plate. Gently seed 200,000 OPCs drop wise on to the DRG neurons as previously described [4][5][6] . NOTE: The total OPC seeding volume must be less than 200 ”l per 22 mm coverslip.…”
Section: Transducing Opcsmentioning
confidence: 99%
“…8. Assess the co-cultures for myelin protein expression by western blot analysis and visualize for the formation of myelinated axonal segments by double-immunostaining with antibodies against myelin basic protein markers and neuronal markers [4][5][6] .…”
Section: Transducing Opcsmentioning
confidence: 99%
See 1 more Smart Citation